Congenital unilateral absence of the upper extremity may give rise to a specific kind of thoracolumbar curve. Issue 2 (March 2018) - Olgun, Z. Deniz; Demirkiran, Gokhan; Polly, David; Yazici, Muharrem
Abstract : There is an increased incidence of scoliosis in patients with congenital malformations of the upper extremity even in the absence of overt vertebral abnormalities. In this case series, we summarize the curve characteristics of four patients presenting to two spine surgery clinics with unilateral amelia or phocomelia and a progressive scoliotic curve with the apex on the side of deficiency. All patients required orthopedic intervention for their curves. Amelia and phocomelia are severe congenital malformations of the upper limb affecting trunk balance and, conceivably, causing scoliosis with the absence of counterbalancing weight on the affected side. The combination of upper limb absence and same-sided scoliosis in these patients may provide a clue of the mechanical factors causing scoliosis in other disorders. In this article, we attempt to define this exceptional deformity, theorize on its etiology, and draw attention to this particular combination of problems. Level of Evidence: Case series; Level IV.